Vietnam land and people - Le, Thong (Vietnam education, 2012)
This book cover in detail the geography, land and people of Vietnam. The purpose of the book is to introduce, in a relatively systemmatic way, the geography, the people, and the economy, as well as the background of Vietnam's terrorial limits and boundaries.